2021
DOI: 10.1080/14712598.2021.1901881
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab for the treatment of chronic rhinosinusitis with nasal polyposis

Abstract: Introduction: Chronic rhinosinusitis with nasal polyps (CRSwNP) affects 1-2.5% of the population and is associated with significant adverse effects on quality of life (QoL). CRSwNP is strongly correlated with (late onset) asthma with 30-70% of the CRSwNP patients having asthma. Health-care spending in rhinosinusitis is high, especially because of indirect costs. Areas covered: In the last years, the recognition of endotyping as an essential presumption to precision medicine has significantly changed the integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 95 publications
1
11
0
1
Order By: Relevance
“…Among the CRSwNP population with adverse effects to dupilumab, women and the elderly are at higher risk of developing adverse events, while male patients are more likely to have severe adverse events [43]. In addition to injection site reaction, nasopharyngitis, headaches, epistaxis, hypereosinophilia, ophthalmic complications, head and neck dermatitis, alopecia areata, and arthritis are occasionally seen during the use of dupilumab [44, 45].…”
Section: Adverse Effects Of Biological Agentsmentioning
confidence: 99%
“…Among the CRSwNP population with adverse effects to dupilumab, women and the elderly are at higher risk of developing adverse events, while male patients are more likely to have severe adverse events [43]. In addition to injection site reaction, nasopharyngitis, headaches, epistaxis, hypereosinophilia, ophthalmic complications, head and neck dermatitis, alopecia areata, and arthritis are occasionally seen during the use of dupilumab [44, 45].…”
Section: Adverse Effects Of Biological Agentsmentioning
confidence: 99%
“…In patients with aspirin-exacerbated respiratory disease (AERD), nasal polyposis can be particularly severe and difficult to control with both pharmacologic and operative interventions [1]. Dupilumab is a monoclonal antibody that inhibits interleukin 4 (IL-4) receptor alpha and is highly effective in reducing nasal polyp burden, preventing recurrent sinus surgery, and reducing sinus infections in patients with severe CRSwNP, particularly those with AERD [2][3][4]. The most common adverse reactions from dupilumab use include temporary injection site reactions, ocular surface reactions, and transient eosinophilia [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have implicated the role of interleukin 13 (IL-13) in inducing damage to olfactory epithelium, suggesting a possible sensorineural anti-inflammatory mechanism. [3][4][5] Studies have also shown a significant reduction in polyp burden after dupilumab, suggesting there may be a conductive component, although this mechanism has not been quantitatively confirmed. 5 The goal of this study is to use computational fluid dynamic modeling (CFD) to examine the potential conductive mechanism of how dupilumab may alleviate olfactory loss in patients with CRSwNP.…”
Section: Introductionmentioning
confidence: 99%